Mal-estar na cidade: ordem e contra-ordem sócio-espacial na cultura do amedrontamento - Soares, Marcus Rosa (2010)
The objective of this thesis consists in analyze the method that fear made its way in the most efficient instrument of social organization in nowadays. It s not the absolute fear, but the spreaded one, the kind of fear that builds the culture of frightening.The conformation of the culture of frightening, the fear not attached at the structural causes that creates it, claims dominant attention at course that, by the hegemonic speech, it s necessary all gear that make real the strategies that fights the fear and uneasiness. These actions are the repressive measures, penal and lethal;the privatization of the public space and, the assurance of the subordination. The dominant actions are building in the juridical, politic, cultural and spacial a craftsmanship discarded by the capitalist way of production in its current globalizated phase. In spite of, as we analyze the specificities of the Brazilian society what is verified is that the culture of the frightening is married to the "black fear", that is, to the stigmatized fear, associate to the discrimination and the prejudice to which the black community is historically submitted. The dominant politics in course in the country denote a clearly defined sense of the ethnic-racial, age and geographical point of view: blacks, young and residents of slums, of popular neighborhoods or from suburbs or of habitational groups are the main victims of the repression of the State and of the violence that kills. The imaginary of the fear in the brazilian society is produced and driven at that share of the population and at those spaces, associating them to the risks and dangers that produce fear and uneasiness to the society. This way its justify the rise of police repression, the escalade of the prison population and the policeman lethality; the loss of prestige of the public space and its swift privatization and; the progress of the politics that make common the"charity capitalism" that contribute to the maintenance hegemonic social spacial order as well as weaken, together with the culture of the frightening, the appearance of strategies and alternative actions against social spacial order. At the end, the possibilities of creation of alternatives to fight the dominant actions of fear. So that they happen are necessary structural, radicals and deep transformations, a true revolution of the politics and democracy that go by through the individual autonomy. From now on, before the addiction that corrupts the traditional forms of doing politics and democracy, are known to be the legitimate social movements, that at first sight, they can act as protagonist of these revolutionary projects and where a real social spacial order can effectively happens.